Enlargement of The Feasibility Analysis of African Catfish in The Tarpaulin Pool in the Hangtuah Village Perhentian Raja District Kampar Regency of Riau Province - Priandari, Cika; Nugroho, Firman; ', Hendrik (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted on 7th February until 14 th February 2013. This study aimed tothe implementation of this study is the know how large the total investment with a different scale inan effort to fish rearing African Catfish ponds in terms of aspects of financial tarpaulin. The methodused in this study is a survey with four respondent .The survey results revealed an effort tarp in the village is divied into three business scalewich is a small scale an 50 m widw, 96 m medium scale enterprises, and large businesses scale an320 m. African catfis aquaculture in the pool tarp several advantages wich have adequate technicaland maintenance more effective African catfish produced a cleaner and more uniform in size. Thehigh price of feed is currently making the amount of catfish farmers in particular to the business ofenlarging the wane when the potential market share fore catfish consumption is still wide open.Total Investment is widely used in small scale enterprises of Rp. 13.842.000,-, while the broadmedium size enterprises amounted to Rp. 26.114.750, and on a large scale enterprise wide Rp.79.538.500,-. Of the third scale, feasibility analysis calculations are profitable and financiallyfeasible to continue to start in medium scale enterprise wide.Keyword : Pool tarp, African catfish, Hangtuah village